Implementasi Metode Kunjungan Lapangan Berbasis Budaya Lokal dalam Meningkatkan Rasa Ingin Tahu Anak - Maghfira Adinda Rahmah Alimuddin; Munirah; Indriani (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Curiosity is one of the essential aspects of early childhood development because it encourages children to actively seek information, explore their environment, and construct knowledge independently. Based on preliminary observations conducted in Group A1 of TK Negeri Pembina Kota Gorontalo, most children demonstrated a low level of curiosity, as indicated by limited questioning, observing, and exploratory behaviors during learning activities. This study aimed to enhance children's curiosity through the implementation of a field trip method based on the introduction of Gorontalo local culture. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 17 children from Group A1 of TK Negeri Pembina Kota Gorontalo. Data was collected through observation and documentation techniques and analyzed using qualitative and quantitative methods. The findings revealed that the implementation of the field trip method significantly improved children's curiosity. The average percentage of curiosity achievement increased from 39.70% in the pre-cycle stage to 46.17% in Cycle I and reached 88.82% in Cycle II. These results indicate that the field trip method based on Gorontalo local culture is effective in fostering children's curiosity through concrete, contextual, and meaningful learning experiences.